ANALISIS TADBIR URUS MAJLIS PERBANDARAN JASIN: IMPLIKASINYA TERHADAP KUALITI HIDUP PENDUDUK DARI PERSPEKTIF MAQĀṢID AL-SHARĪ‘AH: An Analysis on the Governance of Jasin Local Authority: Its Implication Towards Population Quality of Life from the Perspective of Maqāṣid al-Sharī‘ah - Ibrahim, Muhammad Hafiz; Abdul Rahman, Mohamad Zaidi; Md Rasip, Osman (Jurnal Syariah, 2021)
Governance is an important thing for Local Authority to ensure resident’s life in good condition at their administration area. In this study, the Researcher used the quality measure of life from the Malaysian Quality of Life Index 2011 such as housing, environment, health, safety and transportation & communication to explore the impact of local government’s administration on quality of life. The objective of this study is to detect the existence of elements of Maqāṣid al-Sharī‘ah in the quality of life governance of Jasin Municipal Council, to study how the Jasin Municipal Council manage the quality of life of residents under its jurisdiction and to know the extent of Jasin Municipal Council on the issue of quality of life. this study uses a fully qualitative method through the analysis of interviews, documents and observations. Overall, this study shows that the quality and performance of Jasin Municipal Council’s services can affect the quality of life population in its administrative area. Beside that, this study also shows Maqāṣid al-Sharī‘ah should be given a priority on each of their action because Maqāṣid al-Sharī‘ah is an objective to better of life.